Hypokalemic Periodic Paralysis and Renal Tubular Acidosis in Patient withHypothyroidism - Laurensia Goretti; Soebagijo Poegoeh Edijanto (Indian Journal of Forensic Medicine & Toxicology, 2021)
Hypokalemiaperiodic paralysis (HPP) is a rare disorder characterized by acute muscle paralysis. Basedon its etiology, HPP can be classified as primary and secondary types. One of the most common causes ofsecondary HPP is renal tubular acidosis (RTA) which may be also present in thyroid disease. We observed acase of a 48-year-old female, with complaints of weakness in both lower extremities for two days. Difficultiesin walking and weakness in both arms were also present. Patient also experienced nausea, vomiting, anddiarrhea 4 days before coming to the hospital. She had a history of thyroidectomy in 2009 and in 2019 wasadmitted for similar symptoms. Medication consumed by the patient were Euthyrox 100 mg one time dailyand KSR 600 mg three times daily. In the last week, Euthyrox was discontinued by the patient due to herdiarrhea. The patient’s general condition was weak and vital signs were BP 120/80 mmHg, pulse 84 bpm, RR18 times per minute and temperature was 36.6°C. Motoric strength was 4/4 in both arms and 3/3 in both legs.No pathological neurological reflexes were found during examination. Inverted T wave and prominent Uwave were seen on electrocardiogram (ECG) results.Laboratory results showed hypokalemia (2.0 mmol/L),Blood Gas Analysis: Metabolic Acidosis (pH 7.42, pCO2 32 mmHg, HCO3 20.8 mmol/L, BE -3.7 mmol/L)with anion gap of 14.2 meq/L. Urinalysis results were pH 8, urinary anion gap 18.29 mmol/h. Decreasedthyroid function was also shown in the endocrine laboratory panel FT4 0.57 ng/dl and TSH 32.097 IU/mL.HPP is a disorder characterized by muscle weakness and may be present in distal type RTA. Clinicalsymptoms of distal type RTA are hypokalemia, hyperchloremic metabolic acidosis, urinary pH <5.5. Distaltype RTA can be caused by endocrine disorder i.e., hypothyroidism. Observation of patient condition andlaboratory results lead to the conclusion that the patient is diagnosed with hypokalemic periodic paralysisand renal tubular acidosis based on hypokalemia, metabolic acidosis with normal anion gap, and alkalineurine with positive urinary anion gap.